2021
DOI: 10.1007/s00395-021-00866-8
|View full text |Cite
|
Sign up to set email alerts
|

Omecamtiv mecarbil evokes diastolic dysfunction and leads to periodic electromechanical alternans

Abstract: Omecamtiv mecarbil (OM) is a promising novel drug for improving cardiac contractility. We tested the therapeutic range of OM and identified previously unrecognized side effects. The Ca2+ sensitivity of isometric force production (pCa50) and force at low Ca2+ levels increased with OM concentration in human permeabilized cardiomyocytes. OM (1 µM) slowed the kinetics of contractions and relaxations and evoked an oscillation between normal and reduced intracellular Ca2+ transients, action potential lengths and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…For example, a recent study revealed that application of a high dose of OM in rats can induce alternating Ca-transients in the beating cardiomyocytes in parallel to the diastolic dysfunction in the whole heart. 24 In addition, OM affects electrophysiological processes, such as action potential which indirectly regulates intracellular calcium kinetics. 25…”
Section: The General Effect Of Om On Isometric Tension and Ca-transient In Healthy And Failing Rat Myocardiummentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study revealed that application of a high dose of OM in rats can induce alternating Ca-transients in the beating cardiomyocytes in parallel to the diastolic dysfunction in the whole heart. 24 In addition, OM affects electrophysiological processes, such as action potential which indirectly regulates intracellular calcium kinetics. 25…”
Section: The General Effect Of Om On Isometric Tension and Ca-transient In Healthy And Failing Rat Myocardiummentioning
confidence: 99%
“…21,[26][27][28][29] However, it was demonstrated that OM substantially prolongs contraction and relaxation. 18,24 Its use, therefore, may result in unexpected consequences in the species with the physiologically high beat rate (rodents).…”
Section: The Lack Of Negative Inotropism Of Om In Failing Rat Myocardiummentioning
confidence: 99%
“…Finally, the glycation of myofilaments in diabetes, a major risk factor in heart failure, correlates with significant reduction in calcium sensitivity of the sarcomere ( Papadaki et al, 2022 ) that cannot be captured in electrophysiology-only models. The same applies to new drugs directly targeting sarcomere dynamics, e.g., blebbistatin, omecamtiv mecarbil and mavacamten ( Rahman et al, 2018 ; Awinda et al, 2020 ; Fülöp et al, 2021 ): with no in silico contractility description, it is not possible to properly simulate them.…”
Section: Discussionmentioning
confidence: 99%
“…Az OM HF-rEF-betegek funkcionális kapacitására kifejtett hatását a jelenleg folyó METEORIC-HF-vizsgálat fogja tisztázni (26). A plazmakoncentráció rendszeres mérésének szükségessége (technikai és szervezési nehézségek, terápiás céltartomány elérése) és az esetleges, jelenleg még nem ismert mellékhatások korlátozhatják a szer klinikai alkalmazását (27). alapból finanszírozott szakmai támogatásával készült.…”
Section: Megbeszélés Következtetésekunclassified